Emotional maturity of social support with young couples adjustment in early stages of marriage - Tarigan, Noviani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Starting married life is not easy because young couples need to adjust to each other. One of the causes of failure or divorce in marriage is the inability to make self-adjustments properly in young couples. Well-adjusted marriages have lower rates of depression and poorly-adjusted marriages have higher rates of depression. Emotional maturity and social support of young couples are important factors that influence the adjustment of young couples in early marriage. This study is to see how emotional maturity, social support and adjustment of young couples with a sample of 120 people consisting of 60 men and 60 women obtained by purposive sampling technique. Data were taken by distributing instruments of emotional maturity, social support and self-adjustment with a total of 136 statement items. The results were obtained by looking at the percentage value, correlation coefficient and significance value between variables and the results of emotional maturity are in the high category with an R value of 42.5% then the Sig value. (2-tailed) of 0.000 <0.05 (α) so that it is stated to have a significant relationship. Then social support is in the medium category with an R value of 29.8% and a Sig value. (2-tailed) of 0.000 < 0.05 (α) so that it is stated to have a significant relationship. Then self-adjustment is in the high category with an R value of 48.1% and a probability value (Sig. F Change) of 0.000 < 0.05 (α) which means that emotional maturity and social support have a significant and positive relationship with the adjustment of young couples in early marriage.